Institutional Creation as a Local Governance Response to Syrian Refugees: The Case of Turkish Municipalities - Yavcan, Basak; Memisoglu, Fulya (SAGE PUBLICATIONS INC, 2025)
External shocks constitute ideal moments for exploring the creation of new institutions as well as changes within existing ones. This paper treats the influx of Syrian refugees into Turkish urban centers as a critical juncture and investigates the changes in the local governance bodies as a result. Based on interviews and focus group discussions with administrative and nongovernmental actors involved in the local response to refugees, we explore the factors that contributed to the emergence of new institutions within municipalities and their institutionalization as bodies able to resist changes of municipal mayors across elections. We investigate how the newly created institutions matter for refugee policy response in looking at various host cities before and after the 2019 local elections. We argue that actual change in the way institutions operate takes place in municipalities (and their respective departments within) that have managed to institutionalize their refugee response through innovative and sustainable policy initiatives that can spill over to areas of policymaking other than refugee response, which invest in building capacity and multilevel partnerships.
Keywords: Syria; Syrian refugees; Turkey; municipal policy; MIGRATION POLICY; POLITICS; CRISIS; INTEGRATION; Psychology; Social Sciences - Other Topics